Use of Functional MRI in Deep Brain Stimulation in Parkinson's Diseases: A Systematic Review - Miao, Jingya; Tantawi, Mohamed; Koa, Victoria; Zhang, Ashley B.; Zhang, Veronica; Sharan, Ashwini; Wu, Chengyuan; Matias, Caio M. (Frontiers in Neurology, 2022)
Deep brain stimulation (DBS) has been used to modulate aberrant circuits associated with Parkinson’s disease (PD) for decades and has shown robust therapeutic benefits. However, the mechanism of action of DBS remains incompletely understood. With technological advances, there is an emerging use of functional magnetic resonance imaging (fMRI) after DBS implantation to explore the effects of stimulation on brain networks in PD. This systematic review was designed following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines to summarize peer-reviewed articles published within the past 10 years in which fMRI was employed on PD-DBS patients. Search in PubMed database provided 353 references, and screenings resulted in a total of 19 studies for qualitative synthesis regarding study designs (fMRI scan timepoints and paradigm), methodology, and PD subtypes. This review concluded that fMRI may be used in PD-DBS patients after proper safety test; resting-state and block-based fMRI designs have been employed to explore the effects of DBS on brain networks and the mechanism of action of DBS, respectively. With further validation of safety use of fMRI and advances in imaging techniques, fMRI may play an increasingly important role in better understanding of the mechanism of stimulation, as well as in improving clinical care to provide subject-specific neuromodulation treatments.